Paradoxes In Offline FMCG Retailing. New Research Areas For Retailing Management - Sebastian BRAŃKA (Communications of International Proceedings, 2025)
This study relates to the sector of FMCG retailing indicating that it is one of the most significant sectors supplying staple food merchandise to societies worldwide. At the same time the brick&mortar stores are still the dominant channel of FMCG retail sales. Furthermore many authors posit that understanding paradoxes may facilitate managers in acquiring new competences that seem necessary in the contemporary changing world. Undoubtedly the subject of paradoxes does not find much interest among scholars researching problems of contemporary retailing. Therefore one may find publications devoted to single and separate case studies of such self-contradictory situations in retailing management. Therefore we may identify a research gap, namely lack of an overview of the phenomenon of paradoxes in retailing and an attempt to identify and analyse them from a defined perspective and categorize in order to show there multifaceted nature. Thus, the motive behind this study was to highlight the multifaceted notion of paradox in the context of FMCG retailing and attempt to categorize different types of paradoxes in retailing. Regarding the research the author uses a descriptive literature review that concentrated on the notion of paradox in management and in retailing management. Moreover, the author used an overview of empirical data from different markets  in Europe and two case studies in order to illustrate different categories of paradoxes in offline FMCG retailing. This paper uses the perspective of innovation as an axis to present different categories of paradoxes in modern retailing. This leads us to a conclusion that implementation of innovation in management often leads to emergence of paradoxes in retailing. Furthermore the author of the paper has categorized these paradoxes into 3 out of 4 major innovation categories, namely: (1) product innovation, (2) process innovation and (3) organisational innovation.
Keywords: paradoxes in retailing; offline retailing; FMCG retailing